Gundpak, a Milk Khoa Based Traditional Nepalese Product: Production, Marketing and Consumption - Acharya, Pushpa P.; Kharel, Ganga P.; Bhandari, Megha R. (Business, Management and Economics: Research Progress Vol. 5, 2024)
The purpose of the study is to explore a traditional khoa-based Nepalese product gundpak and its tentative production, marketing and consumption. Gundpak, a traditional Nepali sweet, is made from Khoa (partially heat-desiccated milk) and has been a staple in Nepalese cuisine since its introduction in Asan, Kathmandu, in 1933 A.D. The term "Gundpak" combines "Gund" (gum) and "Pakh" (cooked), reflecting its unique preparation involving edible gum. Initially, gundpak was created by ayurvedic practitioner Panna Lal Maskey at Asan, Kathmandu. Gundpak was intended as both a nutritious and medicinal food, particularly beneficial for lactating women and those in need of energy. Gundpak’s popularity has grown, leading to increased domestic and international demand. It is typically produced by the Halwai community and varies significantly in composition due to the lack of standardized recipes. Major ingredients include Khoa, sugar, ghee, and edible gum, with minor ingredients like nuts, spices, and dried fruits enhancing flavor and texture. Two main types exist: Normal Gundpak, which excludes medicinal ingredients, and medicinal gundpak, which includes battisa powder and Jesthalwangadi, used for its health benefits. Production involves cooking khoa with sugar and ghee, integrating gum and other ingredients, followed by cooling and packaging. The cooking process relies on traditional methods using stoves and open pans, with variations in ingredients and methods depending on the manufacturer. Consumer preferences indicate a strong inclination toward gundpak's texture, color, and flavor. Most respondents prefer a semi-soft texture, with sugar and gum being key contributors to its quality. Gundpak's shelf life is typically one week in summer and up to two weeks in winter. In summary, Gundpak reflects a rich tradition of Nepali confectionery, with variations in production and consumption patterns contributing to its enduring appeal.